Gifts from the earth - Thomas, Theodore; Skinner, Thomas ([S.l.]: Amazon)
Investigates the dwindling store of mineral wealth that provides the fundamental building blocks of our technology. Explore incredible geological resources like the eerie'black smokers' - hot springs located on the ocean floor that have created abundant deposit over millions of years
Project director & executive producer, Thomas Skinner
Narrated by Richard Kiley
Keywords: Mines and mineral resources; Earth